Beinvloedingspatrone van Kommunikasieklimaat op Organisasiegedrag - Sonja Verwey (Communicare)
THIS article examines the patterns of influence that exist between organisational behaviour and communication climate. A comprehensive over view of the literature and research findings form the basis of this discussion. From this discussion It is evident that communication is a very important process in the organisation and that management is becoming increasingly aware of the influence that communication climate exerts on a wide range of organisational behaviours.